2017
DOI: 10.5194/amt-2017-106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying TOLNet Ozone Lidar Accuracy during the 2014 DISCOVER-AQ and FRAPPÉ Campaigns

Abstract: Abstract. The Tropospheric Ozone Lidar Network (TOLNet) is a unique network of lidar systems that measure high-resolution atmospheric profiles of ozone. The accurate characterization of these lidars is necessary to determine the uniformity of cross-instrument calibration. From July to August 2014, three lidars, the TROPospheric OZone (TROPOZ) lidar, the Tunable Optical Profiler for Aerosol and oZone (TOPAZ) lidar, and the Langley Mobile Ozone Lidar (LMOL), of TOLNet participated in the Deriving Information on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As part of these efforts, TOLNet lidar teams have collectively developed rigorous instrument procedures and processing algorithms to ensure consistency in O 3 data products and associated uncertainties between instruments (Leblanc et al, 2016a, b). Crosscomparison studies conducted between TOLNet lidar systems (Leblanc et al, 2018;Wang et al, 2017;Sullivan et al, 2015) showed that O 3 profile concentrations typically agree within ±5%, consistent with system specific propagated errors.…”
Section: The Langley Mobile Ozone Lidar (Lmol)mentioning
confidence: 56%
See 1 more Smart Citation
“…As part of these efforts, TOLNet lidar teams have collectively developed rigorous instrument procedures and processing algorithms to ensure consistency in O 3 data products and associated uncertainties between instruments (Leblanc et al, 2016a, b). Crosscomparison studies conducted between TOLNet lidar systems (Leblanc et al, 2018;Wang et al, 2017;Sullivan et al, 2015) showed that O 3 profile concentrations typically agree within ±5%, consistent with system specific propagated errors.…”
Section: The Langley Mobile Ozone Lidar (Lmol)mentioning
confidence: 56%
“…TOLNet lidar systems have contributed to a wide range of atmospheric studies, including DISCOVER-AQ, FRAPPÉ CABOTS, FAST-LVOS, etc. (Wang et al, 2017;Sullivan et al, 2015;Johnson et al, 2018;Langford et al, 2018). As part of these efforts, TOLNet lidar teams have collectively developed rigorous instrument procedures and processing algorithms to ensure consistency in O 3 data products and associated uncertainties between instruments (Leblanc et al, 2016a, b).…”
Section: The Langley Mobile Ozone Lidar (Lmol)mentioning
confidence: 99%
“…Duvall et al () describe an effort to assess the usefulness of low‐cost sensors for ozone and NO 2 for scientific studies. FRAPPÉ measurements were also used to improve the accuracy and applicability of TOLNet (Tropospheric Ozone LIDAR Network, https://www-air.larc.nasa.gov/missions/TOLNet/) measurements for large‐scale air quality studies (Wang et al, ).…”
Section: Measurement Resources and Sampling Strategymentioning
confidence: 99%
“…This residual O 3 will then influence the “starting” mixing ratio as O 3 production begins. There can be considerable variability in this residual O 3 (McDuffie et al, ), but without coincident O 3 LIDAR measurements at BAO such as those during summer 2014 (Wang et al, ), it is difficult to estimate. We also expect that PAN and PPN will remain aloft in the residual layer and that they are likely also entrained into the planetary boundary layer during the next day.…”
Section: Resultsmentioning
confidence: 99%